2017
DOI: 10.1007/s11121-017-0809-x
|View full text |Cite
|
Sign up to set email alerts
|

Advances in EBI Development for Diverse Populations: Towards a Science of Intervention Adaptation

Abstract: This introduction examines major issues and challenges as presented in this special issue of Prevention Science, “Challenges to the Dissemination and Implementation of Evidence Based Prevention Interventions for Diverse Populations.” We describe the Fidelity-Adaptation Dilemma that became the origin of dynamic tensions in prevention science. It generated controversies and debates and new perspectives on the dissemination and implementation of evidence-based interventions (EBIs) within diverse populations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 37 publications
1
80
0
Order By: Relevance
“…In this project, significant adaptation was needed at the paradigm level in addition to the implementation level, which included engaging Karen knowledge and meaning around addiction, treatment, and recovery. Additionally, and consistent with findings by Epstein et al (2015), Castro & Yasui (2017), and Barrera et al (2013), this project also demonstrated that developing deep collaborative partnerships with the target community was essential for achieving mutual adaptation. It offers several suggestions for facilitating mutual learning and adaptation related to equalizing power, learning about and being responsive to different communication styles, recognizing the cultural context of all knowledge, building sustainable institutional partnerships, and building individual and organizational capacity to participate toward mutual goals.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this project, significant adaptation was needed at the paradigm level in addition to the implementation level, which included engaging Karen knowledge and meaning around addiction, treatment, and recovery. Additionally, and consistent with findings by Epstein et al (2015), Castro & Yasui (2017), and Barrera et al (2013), this project also demonstrated that developing deep collaborative partnerships with the target community was essential for achieving mutual adaptation. It offers several suggestions for facilitating mutual learning and adaptation related to equalizing power, learning about and being responsive to different communication styles, recognizing the cultural context of all knowledge, building sustainable institutional partnerships, and building individual and organizational capacity to participate toward mutual goals.…”
Section: Discussionsupporting
confidence: 82%
“…A systematic review of adaptation methods found that out of 31 studies only 14 included consultation with members of the community of interest in the process of cultural adaptation (Healey et al, 2017). Despite this finding, most adaptation frameworks highlight the importance of collaboration or consultation with members of the target community in adaptation procedures (Barrera et al, 2013;Castro & Yasui, 2017;Epstein et al, 2015). One of the authors of this paper has articulated a framework for a collaborative approach to integration (Cook, 2016).…”
mentioning
confidence: 99%
“…The field of implementation science increasingly calls for studies to examine how evidence-based practices are adapted and sustained over time [63]. Understanding how HV programs adapt interventions with fidelity [64] and what factors they need to sustain evidencedbased practices are key areas for future investigation. Such research may also demonstrate the long-lasting impact of CQI efforts on HV programs' ability to address such pernicious health issues as postpartum depression.…”
Section: Plos Onementioning
confidence: 99%
“…It is promising to see that all, except one program were either culturally adapted or cultural-based programs. Cross-cultural translation of prevention concepts is important for programs to be appropriate and effective for the target group (Castro and Yasui 2017;Dickerson et al 2018). The most common setting for programs was schools, which have the potential to reach many young people and has been identified as a priority setting for prevention (Barry et al 2013).…”
Section: Outcomes Type Setting and Context Of Prevention For Indigementioning
confidence: 99%
“…Substance use prevention strategies have shown to be effective for non-Indigenous adolescents, including school-based, community-based and family-based programs (Foxcroft and Tsertsvadze 2012;Newton et al 2017). Given the unique historical and cultural contexts, non-Indigenous programs likely require a cross cultural translation for Indigenous adolescents, mapped against different communication styles and language, accounting for situational and place context, and different perspectives of health and identity (Castro and Yasui 2017;Dickerson et al 2018). Programs adapted from existing non-…”
Section: Introductionmentioning
confidence: 99%